Transthoracic Ultrasound in Infectious Organizing Pneumonia: A Useful Guide for Percutaneous Needle Biopsy - Lacedonia, Donato; Quarato, Carla Maria Irene; Borelli, Cristina; Dimitri, Lucia; Graziano, Paolo; Foschino Barbaro, Maria Pia; Scioscia, Giulia; Mirijello, Antonio; Maggi, Michele Maria; Rea, Gaetano; Ferragalli, Beatrice; De Cosmo, Salvatore; et al. (Frontiers in Medicine, 2021)
In patients presenting with classical features of CAP (i.e., new peripheral pulmonary consolidations and symptoms including fever, cough and dyspnea) a clinical response to the appropriate therapy occurs in few days. When clinical improvement has not occurred and chest imaging findings are unchanged or worse, a more aggressive approach is needed in order to exclude other non-infective lesions (including neoplasms). International guidelines do not currently recommend the use of transthoracic ultrasound (TUS) as an alternative to chest X-ray (CXR) or chest computeed tomography (CT) scan for the diagnosis of CAP. However, a fundamental role for TUS has been established as a guide for percutaneous needle biopsy (US-PNB) in pleural and subpleural lesions. In this retrospective study we included 36 consecutive patients whose final diagnosis, made by a US-guided percutaneous needle biopsy (US-PTNB), was infectious organizing pneumonia (OP). Infective etiology was confirmed by additional information from microbiological and cultural studies or with a clinical follow-up of 6-12 months after a second line antibiotic therapy plus corticosteroids. All patients have been subjected to a chest computed tomography (CT) and a systematic transthoracic ultrasound (TUS) examination before biopsy. This gave us the opportunity to explore TUS performance in assessing CT findings of infective OP. Although ultrasound findings did not allow to characterize chronic subpleural lesions, TUS confirmed to be a valid diagnostic aid for guiding percutaneous needle biopsy of subpleural consolidations.